Apuntes sobre anatomía y morfología de las semillas de cactáceas. II. Caracteres de valor taxonómico - Flores, Eugenia M. (Revista de Biología Tropical, 1976)
Histological investigations were made of ovules and seeds of 18 species of Cactaceae representing the three tribes (or subfamilies) usually recognized. Fifteen characteristics of ovules and seeds are discussed. On the basis of these fifteen characters the three traditional tribes (Pereskieae, Careeae and Opuntieae) may be recognized; also several subgroups may be proposed in the Cereeae. The embryo appears to offer unusual possibilities in suggesting relationships between species, especially when employed together with other histological studies. AH lines of evidence point to the fact that the Opuntieae and the Pereskieae are quite natural taxa, while the Cereeae appears to be a very heterogeneous taxon.